2008
DOI: 10.1002/bies.20823
|View full text |Cite
|
Sign up to set email alerts
|

Shaping segments: Hox gene function in the genomic age

Abstract: Despite decades of research, morphogenesis along the various body axes remains one of the major mysteries in developmental biology. A milestone in the field was the realisation that a set of closely related regulators, called Hox genes, specifies the identity of body segments along the anterior-posterior (AP) axis in most animals. Hox genes have been highly conserved throughout metazoan evolution and code for homeodomain-containing transcription factors. Thus, they exert their function mainly through activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
117
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(117 citation statements)
references
References 124 publications
0
117
0
Order By: Relevance
“…The epigenetic control of gene expression has been best studied for the control of homeotic gene expression (33,57), which is established during embryogenesis and maintained throughout animal life. However, not only homeotic genes are regulated through epigenetic modifications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The epigenetic control of gene expression has been best studied for the control of homeotic gene expression (33,57), which is established during embryogenesis and maintained throughout animal life. However, not only homeotic genes are regulated through epigenetic modifications.…”
Section: Resultsmentioning
confidence: 99%
“…The best-characterized targets of H3K27me3/Pc-mediated silencing are homeotic genes, which are critical regulators of animal patterning (33,57). However, many other genes are also enriched for H3K27 methylation and Pc binding (5,6,45,53,65,72,76).…”
mentioning
confidence: 99%
“…Our genome-wide study provides a firm demonstration of a view previously suggested by genetics that Ubx is a micromanager in the haltere: it modulates the wing program by interacting with the wing transcriptional network at multiple levels and over many developmental stages, controlling the expression of numerous target genes with a wide range of functions. However, there is also evidence for other modes of Hox gene action (4)(5)(6)(7)(8). For example, the role of Abdominal B in Drosophila posterior spiracles is more akin to that of a master control gene (30).…”
Section: Discussionmentioning
confidence: 99%
“…It has been further complicated by the functional redundancy of the Hox proteins and the cross-regulatory interactions between them. These factors have made it difficult to elucidate the complete set of target genes modulated by any one Hox gene over the course of a single developmental process (3)(4)(5)(6)(7)(8). Thus, it remains an open question of how these widely conserved patterning genes link to the actual effectors of cell and organ morphology at a genome-wide level over time.…”
mentioning
confidence: 99%
“…Some PAH-repeat-containing proteins are known to function as components of co-repressor complexes in transcriptional silencing (Wang et al, 1990). SANT and homeodomains function in the regulation of transcription (Boyer et al, 2004;Hueber and Lohmann, 2008). Interestingly, BLAST searches revealed that the PAH repeats of Mute-L are 28% identical to that of zebrafish Ugly duckling (Udu), a nuclear protein required for somite development (Lim et al, 2009;Liu et al, 2007) and 27% identical to that of human GON4L or YARP (YY1AP-related protein 1), a nuclear protein with suggested transcriptionalregulator-like functions (supplementary material Fig.…”
Section: Identification and Molecular Cloning Of Mutementioning
confidence: 99%